2020
DOI: 10.3390/microorganisms8040535
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Pectin on Mucosal Innate Immune Function in Pigs Mediated by Gut Microbiota

Abstract: The use of prebiotics to regulate gut microbiota is a promising strategy to improve gut health. Pectin (PEC) is a prebiotic carbohydrate that enhances the health of the gut by promoting the growth of beneficial microbes. These microbes produce metabolites that are known to improve mucosal immune responses. This study was conducted to better understand effects of PEC on the microbiome and mucosal immunity in pigs. Pigs were fed two diets, with or without 5% apple PEC, for 72 days. Effects of PEC on the microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 72 publications
3
25
0
Order By: Relevance
“…However, an increased abundance of Proteobacteria has been observed in humans with enteric infections, colorectal cancer, and metabolic syndrome, and may be a microbial signature of dysbiosis in the gut microbiota [ 45 ]. In young pigs, undigested dietary proteins in the gastrointestinal tract enter the hindgut and become a substrate of fermentation by some genera belonging to Proteobacteria , such as E. coli , Klebsiella spp., and Campylobacter spp [ 46 ]. Conversely, these undigested dietary proteins promote the reproduction of these harmful bacteria [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increased abundance of Proteobacteria has been observed in humans with enteric infections, colorectal cancer, and metabolic syndrome, and may be a microbial signature of dysbiosis in the gut microbiota [ 45 ]. In young pigs, undigested dietary proteins in the gastrointestinal tract enter the hindgut and become a substrate of fermentation by some genera belonging to Proteobacteria , such as E. coli , Klebsiella spp., and Campylobacter spp [ 46 ]. Conversely, these undigested dietary proteins promote the reproduction of these harmful bacteria [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha diversity is characterized as the diversity of species richness in a speci c area or ecosystem [24,25]. In our study, Simpson, Shannon, and Chao1 richness were signi cantly increased in FSBM groups compared with the SBM group, which can explain by the suitable growth ecosystem for the microbes because of the organic acid and probiotic of the FSBM group.…”
Section: Discussionmentioning
confidence: 49%
“…Over the years, numerous studies have shown the beneficial effects of pectin and its potential to regulate the inflammatory response (Li et al, 2020), cholesterol (Zofou et al, 2019), and blood glucose (Carvalho et al, 2019). Previous study in our laboratory showed that dietary supplementation of pectin could enhance intestinal barrier function (Wen et al, 2022), increase the expression of Claudin-4 and Muc-2 in the cecum of piglets (Wu et al, 2020), and abolish the abnormal expression of ZO-1 and Occludin caused in the acute pancreatitis model (Xiong et al, 2021). In this study, pectin supplementation could improve gut barrier function to alleviate LPS-induced intestinal injury in the cecum by increasing the number of goblet cells, and improving the expression of tight junction proteins and Muc-2.…”
Section: Discussionmentioning
confidence: 89%
“…Beyond that, the effect of microbial metabolites (short-chain fatty acids) is a non-negligible regulatory pathway. Pectin is mainly a group of acids heteropolysaccharides consisting of D-galacturonic Acids (D-Gal-A) linked by α-1,4-glycosidic bonds (Wu et al, 2020). Besides, it also contains neutral sugars, such as L-rhamnose, D-galactose, and D-arabinose.…”
Section: Introductionmentioning
confidence: 99%